Adoption of M-Learning in Business English Course and Its Relationship to Learning Style Preferences: An Empirical Investigation - Xiaojun Cao; Xiaojun Cao (Frontiers in Psychology, 2022)
Learning around the world has been changed with the rapid development in technology which promotes the students to be more flexible and interactive with each other which has been encouraged by the mobile learning environment. Therefore, the current study intends to analyze the impact of inquiry learning, reflective thinking on problem-solving skills, and critical thinking skills with the mediation of peer communication. To carry out the study, data was collected from 378 college students in China by using survey forms. The analysis of the data and validation of the proposed hypotheses were conducted using Smart-PLS and structural equation modeling (SEM) technique. The results revealed that inquiry learning and reflective thinking affect problem-solving skills. However, inquiry learning and reflective thinking did not affect critical thinking skills. Moreover, the study found that peer communication mediated the relationship between reflective thinking, problem-solving skills, and between reflective thinking and critical thinking skills. However, peer communication did not mediate the relationship among inquiry learning as independent variable and problem-solving skills and critical thinking skills as dependent. The study has theoretically contributed by examining the impact of online learning styles on higher-order thinking skill (HOTS) in the M-learning environment. Also, the study greatly advances the literature by investigating the mediating role of peer communication. Practically, the colleges can improve the students HOTS by devising policies and educational programs focusing on learning styles.